Challenges of Online Boarding Schools In The Digital Era - Kardi Kardi; Hasan Basri; Andewi Suhartini; Fitri Meliani (At-tadzkir: Islamic Education Journal, 2023)
The virtual world has caused disruption in various social lives and institutions, including Islamic boarding schools. This oldest religious institution in Indonesia has also redefined its meaning, thus building a new stream called "Pesantren Online" (online Islamic school) which changes people's perception of the pesantren itself. As a means of religious learning, Islamic Boarding Schools Online, in this case, the website www.pesantrenvirtual.com, try to satisfy people's desires for religious matters. This paper concludes that the human need to get information about religious themes instantly triggers the creation of religious online sites, such as pesantrenvirtual.com, as a reference to overcome the confusion of religious surfers.